CHERNOBYL ACCIDENT: RATIONALE AND REALIZATION OF DECISIONS ON PROTECTION OF THE POPULATION - Yu. O. Konstantinov (Радиационная гигиена)
Regulation of decision making on protection of the public from radiation exposure caused by the Chernobyl accident is retrospectively reviewed. Decisions on prime countermeasures such as evacuation of population from 30 km zone around the Chernobyl nuclear power plant were taken on the ground of a priori developed criteria. The next years, elaboration of a set of regulating documents was needed for implementation of countermeasures corresponding to real conditions of unprecedented scale and levels of radioactive contamination of large territory. Within several years the temporary permissible levels of radiation exposure and content of radionuclides in foodstuff were adopted for current operative decisions. The subsequent decisions made under a pressure of sociopolitical circumstances resulted in a compromise between radiation protection principles and inadequate public perception of radiological risk. Now a decision is needed to solve a problem of the return of radioactively contaminated territories to normal life. The analysis of experience gained in overcoming of consequences of the Chernobyl accident is of great importance for perfection of readiness for management of radiological emergencies.